Cardioprotective Effect of the Aqueous Extract of Lavender Flower against Myocardial Ischemia/Reperfusion Injury - Dong Wang; Xin Guo; Mingjie Zhou; Jichun Han; Bo Han; Xiling Sun (Journal of Chemistry)
This study was conducted to evaluate the cardioprotective property of the aqueous extract of lavender flower (LFAE). The myocardial ischemia/reperfusion (I/R) injury of rat was prepared by Langendorff retrograde perfusion technology. The heart was preperfused with K-H solution containing LFAE for 10 min before 20 minutes global ischemia, and then the reperfusion with K-H solution was conducted for 45 min. The left ventricular developed pressure (LVDP) and the maximum up/downrate of left ventricular pressure (±dp/dtmax) were recorded by physiological recorder as the myocardial function and the myocardial infarct size was detected by TTC staining. Lactate dehydrogenase (LDH) and creatine kinase (CK) activities in the effluent were measured to determine the myocardial injury degree. The superoxide anion dismutase (SOD) and malondialdehyde (MDA) in myocardial tissue were detected to determine the oxidative stress degree. The results showed that the pretreatment with LFAE significantly decreased the myocardial infarct size and also decreased the LDH, CK activities, and MDA level, while it increased the LVDP, ±dp/dtmax, SOD activities, and the coronary artery flow. Our findings indicated that LFAE could provide protection for heart against the I/R injury which may be related to the improvement of myocardial oxidative stress states.